Evaluating universities' strategic online communication: how do Shanghai Ranking's top 50 universities grow stakeholder engagement with Facebook posts?. Issue 3 (10th May 2020) - Fähnrich, Birte; Vogelgesang, Jens; Scharkow, Michael
Abstract : Purpose: This study is dedicated to universities' strategic social media communication and focuses on the fan engagement triggered by Facebook postings. The study contributes to a growing body of knowledge that addresses the strategic communication of universities that have thus far hardly dealt with questions of resonance and evaluation of their social media messages. Design/methodology/approach: Using the Facebook Graph API, the authors collected posts from the official Facebook fan pages of the universities listed on Shanghai Ranking's Top 50 of 2015. Specifically, the authors retrieved all posts in a three-year range from October 2012 to September 2015. After downloading the Facebook posts, the authors used tools for automated content analysis to investigate the features of the post messages. Findings: Overall, the median number of likes per 10, 000 fans was 4.6, while the number of comments (MD = 0.12) and shares (MD = 0.40) were considerably lower. The average Facebook Like Ratio of universities per 10, 000 fans was 17.93%, the average Comment Ratio (CR) was 0.56% and the average Share Ratio (SR) was 2.82%. If we compare the average Like Ratios (17.93%) and Share Ratios (2.82%) of the universities with the respective Like Ratios (5.90%) and Share Ratios (0.45%) of global brands per 10, 000 fans, we may find that universities are three times (likes) and six times (shares) as successful as are global brands in triggering engagement among their fan bases. Research limitations/implications: The content analysis was solely based on the publicly observable Facebook communication of the Top 50 Shanghai Ranking universities. Furthermore, the content analysis was limited to universities listed on the Shanghai Ranking's Top 50. Also, the Facebook posts have been sampled between 2012 and September 2015. Moreover, the authors solely focused on one social media channel (i.e., Facebook), which might restrict the generalizability of the study findings. The limitations notwithstanding, university communicators are invited to take advantage of the study's insights to become more successful in generating fan engagement. Practical implications: First, posts published on the weekend generate significantly more engagement than those published on workdays. Second, the findings suggest that posts published in the evening generate more engagement than those published during other times of day. Third, research-related posts trigger a certain number of shares, but at the same time these posts tend to lower engagement with regard to liking and commenting. Originality/value: To the authors' best knowledge, the automated content analysis of 72, 044 Facebook posts of universities listed in the Top 50 of the Shanghai Ranking is the first large scale longitudinal investigation of a social media channel of higher education institutions.